2003
DOI: 10.1002/cb.131
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fragrance on consumer choice

Abstract: The following research focuses on fragrance (sense of smell) as a primary driver in consumer choice. The fragrance industry is also discussed, along with the impact of atmospherics and the surrounding environment on the consumer. A case study on bar soaps shows how changes to the product fragrance or packaging can affect the purchase decision.The learning and recommendations apply directly to the formation of marketing strategy and are particularly important to categories such as body cleaning and other catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 16 publications
1
47
1
5
Order By: Relevance
“…67).'' The bulk of the research to date that tests consumer reactions to scent has focused on ''localized'' scent (Gulas and Bloch, 1990), or scented objects used as promotional items (Morrin and Ratneshwar, 2000) and product scents like those found in household cleaners and shampoos (Bone and Jantranis, 1992;Milotic, 2003).…”
Section: Ambient Scentmentioning
confidence: 99%
“…67).'' The bulk of the research to date that tests consumer reactions to scent has focused on ''localized'' scent (Gulas and Bloch, 1990), or scented objects used as promotional items (Morrin and Ratneshwar, 2000) and product scents like those found in household cleaners and shampoos (Bone and Jantranis, 1992;Milotic, 2003).…”
Section: Ambient Scentmentioning
confidence: 99%
“…Yet, consumers’ decision‐making processes are also influenced by other sensory information. Marketers understand that auditory and visual influences alone can be insufficient to persuade consumers and that increased persuasiveness can be achieved by targeting the senses of touch, taste and smell (Milotic, ; Lwin and Morrin, ). The marketing strategy of appealing to all five senses is referred to as sensory or experiential marketing (Hultén et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that physical environment can alter consumers' emotions. For example, Milotic (2003) and Mitchell, Kahn, and Knasko (1995) to a given emotional state. It is thus apparent that the development of emotional value can be affected by the consumption environment (Foxall & Greenly, 1999).…”
Section: Physical Environment and Contact Personnel Performance Effecmentioning
confidence: 99%